Putredophytes in the bryoflora of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
A large number of bryophyte species grow on certain substrates as rotten remnants of plants, animals and fungi. In the bryoflore of Ukraine, 134 such species were previously detected – out of them 77 species of Bryophyta and 57 of Marchantiophyta, representing 15,8 % of the species composition. However, this substrate group is not typified, does not have a short, single–word name, which would characterize the features of these species. It is proposed to name it putredophytes (from the latin pútredo – rotting, quasi lignum putridum – rotten wood). Putredophytes are not epixiles, as epixiles grow on the bare wood of trunks, branches and stumps of the trees until these substrates start decomposing and the decay processes become well visible. Putredophytes habitats are not only rotten wood of different stages of rotting but also decayed remains of herbaceous plants, rotten forest floor, decomposed remains of fungi, lichens, other mosses, animal remains and excrements, decomposed objects of human activity at various stages of decay (for example, thrown shoes, clothes, etc.). Among the bryoputredophytes, five groups are distinguished in relation to the putredosubstrates and to other types of substrates, on which these types of mosses are located: group I – euputrédophytes (greek eu – good, well + putredophytes) – 17 species of putredobryoflora; group II – subputredophytes (latin sub – + putredophytes) – 25 species; group III – mesoputredophytes (greek mesos – medium + putredophytes) – 41 species; group IV – oligoputredophytes (greek ολίγος – a little + putredophytes) – 30 species); group V – pauloputredophytes (latin paulo – a little bit, little, slightly + putredophytes) – 21 species.
Keywords: Bryophytes, euputredophytes, subputredophytes, mesoputredophytes, oligoputredophytes, pauloputredophytes.